Reducing unnecessary regulatory burden: The Philippine tuna industry - Gilberto M. Llanto; Ma. Kristina P. Ortiz; Cherry Ann D. Madriaga (Philippine Institute for Development Studies (PIDS), 2017)
The Philippine fishing industry is considered as one of the major industries in the agriculture and fisheries sector. The marine resources available to the country indicate its vast potential in employment creation and output growth. It is in this light that the research team conducted this study with special focus on the tuna industry. The study objectives are to (a) provide regulatory mapping imposed on the local tuna industry; (b) identify those regulations considered as unnecessary or too burdensome to the industry; and (c) provide some recommendations on removing unnecessary regulations. An important inclusion in this project is the Informed Regulatory Conversation which allows the regulators and the private sector to discuss the identified issues and come up with unified recommendations to ease the regulatory burden on different tuna industry stakeholders. The result of the regulatory mapping shows the extent and number of regulations affecting the industry. Overall, the regulations imposed on the industry, especially those concerned with food safety standards, make sense and are necessary. However, there is a case for improving the regulatory framework of the tuna industry, especially the procedures for registration, licensing, and inspection as discussed in detail in the report. The regulatory issues that were identified by the team basically focused on a) acquiring business permit; b) acquiring registration and licenses for all types of fishing vessels from MARINA, BFAR, and the local government unit; c) acquiring License to Operate from the FDA and the possible case of duplication of inspection process by the BFAR and FDA; d) acquiring Certificate of Product Registration from the FDA; e) the Qualified Person in Industry Regulatory Affairs of FDA; and f) presence of BFAR signatories for the regulatory instruments, among others. Agreements to solve the regulatory burden to address the issues are detailed in the report.
Keywords: 330; regulatory impact analysis; regulatory burden; regulations; cost of doing business; tuna industry; Hazard Analysis of Critical Control Points; license to operate; business permit